Development of Lucky Draw Chemist Based on the Website as Learning Media to Improve Students Analysis Skills in Chemical Bonding Material - Sukma, Shinta Irawati; Rusmini, Rusmini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The difficulty in understanding chemistry material generally is caused by the process of conveying information that is not optimal between teachers and students. Therefore, an effort is needed to optimize chemistry learning in the classroom. Learning media is required to improve students' analysis skills in the continuity of a good learning process. There are many types of learning media, one of which is in the form of a website. This study aims to develop the Lucky Draw Chemist media based on the website to improve students' analysis skills in chemical bonding material. This study refers to a 4D design with three stages: define, design, and development. The target of this study is the feasibility of the Lucky Draw Chemist media based on the website based on expert assessment (Chemistry lecturers and chemistry teachers). The results showed that the validity obtained in each assessment aspect was ≥ 4, with the category